2018
DOI: 10.1155/2018/3758506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dust Storms and Climatological Factors on Mortality and Morbidity of Cardiovascular Diseases Admitted to ED

Abstract: Objective This study was designed to investigate the effects of Desert Dust Storms and Climatological Factors on Mortality and Morbidity of Cardiovascular Diseases admitted to emergency department in Gaziantep. Method Hospital records, obtained between September 01, 2009 and January 31, 2014, from four state hospitals in Gaziantep, Turkey, were compared to meteorological and climatological data. Statistical analysis was performed by Statistical Package for the Social Science (SPSS) for windows version 24.0. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Of the selected studies, only 8 provided information on the impact of PM 10 -dust on the incidence of ACS [ 14 , 24 , 25 , 28 , 29 , 30 , 31 , 32 ], comprising a total of 128,633 events. For lag 0 in relation to ACS, the impact of PM 10 -dust was IRR = 1.002 (95% CI 0.999–1.004); p = 0.144; I 2 = 0%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the selected studies, only 8 provided information on the impact of PM 10 -dust on the incidence of ACS [ 14 , 24 , 25 , 28 , 29 , 30 , 31 , 32 ], comprising a total of 128,633 events. For lag 0 in relation to ACS, the impact of PM 10 -dust was IRR = 1.002 (95% CI 0.999–1.004); p = 0.144; I 2 = 0%.…”
Section: Resultsmentioning
confidence: 99%
“…In June 2020, a tremendous plume of dust from North Africa was detected approaching the USA and other countries ( Figure 5 and Supplementary Materials Video S1).The intensity and extent of the plume was so great that it blanketed the Caribbean Sea and darkened skies in several states in the USA [34]. Different studies conducted individually in different regions have evaluated the relationship between desert dust and ACS [14,24,25,[28][29][30][31][32] and heart failure [25,29,30,33]. In our opinion, the number of studies made is clearly insufficient to be able to draw conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-three articles from almost all regions discussed mortality due to dust storms by means of different health problems, such as increased total non-accidental deaths, 3 , 38 , 39 , 41 , 46 , 53 - 55 , 68 - 82 cardiovascular deaths, 3 , 38 , 39 , 48 , 50 , 53 , 70 , 74 , 77 , 82 - 85 mortality due to acute coronary syndrome ( ACS), 3 , 70 , 81 , 86 and respiratory mortality. 48 , 53 , 55 , 77 , 87 Some studies reported, however, that the number of cases was not increased significantly for all-causes, 43 , 88 respiratory, 38 , 43 cardiovascular, 43 or cerebrovascular mortality.…”
Section: Short-term Health Effectsmentioning
confidence: 99%
“…A seasonal episode of Asian sand dust (ASD), which originates from arid areas of Mongolia and the Gobi desert, and affects the Korean peninsula, Japan, and China, is a major source of pollution in the East and Northeast Asia (Jung, 2016). In recent years, a growing number of reports have suggested that ASD exposure negatively affects human health, leading to respiratory diseases (Jung et al, 2012;Yu et al, 2012;Watanabe et al, 2016;Nakao et al, 2018) and significant mortality annually (Chen et al, 2004;Lee et al, 2014;Al et al, 2018). In addition, ASD contains PM of diameters < 10 µm (PM 10 ) along with inhalable hazardous chemical components such as sulfate (SO 4 2− ) and nitrate (NO 3 − ) and microbes such as bacteria, viruses, and fungi (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%